Population Structure and Genetic Diversity Analysis of Germplasm from the Winter Wheat Eastern European Regional Yield Trial (WWEERYT). Issue 2 (3rd January 2017) - Beil, Craig T.; Manmathan, Harish K.; Anderson, Victoria A.; Morgounov, Alexey; Haley, Scott D.
Abstract : Characterization of population structure and genetic relatedness within wheat ( Triticum aestivum L.) germplasm collections is critical for genomewide association studies (GWAS) and training population development for genomic selection (GS). Cooperative regional or international nurseries are well suited for GWAS and GS studies due to the availability of multi‐environment datasets that are often produced. In this study, we analyzed population structure and genetic diversity of 283 genotypes from 7 yr of the Winter Wheat Eastern European Regional Yield Trial (WWEERYT). The collection was genotyped with single‐nucleotide polymorphism (SNP) markers obtained via genotyping‐by‐sequencing; a subset of 548 highly polymorphic SNPs was used for all analyses. Population structure was composed of seven subpopulations when using a correlated allele frequencies model in the program STRUCTURE. The genotype's breeding program of origin was closely related to, but not a perfect indicator of, subpopulation assignment. Genotypes of Central and Eastern European origin were assigned to six of the seven subpopulations, while genotypes from the United States were assigned to only two of the seven subpopulations. The lowest value for Wright's fixation index observed ( F ST = 0.20) was between a population of predominately Turkey‐CIMMYT‐ICARDA genotypes and genotypes from the United States, indicating a close relationship between genotypes from these two regions. The characterization of population structure and genetic diversity within the WWEERYT nurseries will allow breeders to accurately select and test germplasm that is genetically diverse from their own by targeting germplasm from different subpopulations identified under model 1. The results presented in this paper will help to foster the utilization and exchange of WWEERYT germplasm across diverse global winter wheat production regions.